Protein aggregate formation permits millennium-old brain preservation. Issue 162 (8th January 2020) - Petzold, Axel; Lu, Ching-Hua; Groves, Mike; Gobom, Johan; Zetterberg, Henrik; Shaw, Gerry; O'Connor, Sonia
Abstract : Human proteins have not been reported to survive in free nature, at ambient temperature, for long periods. Particularly, the human brain rapidly dissolves after death due to auto-proteolysis and putrefaction. The here presented discovery of 2600-year-old brain proteins from a radiocarbon dated human brain provides new evidence for extraordinary long-term stability of non-amyloid protein aggregates. Immunoelectron microscopy confirmed the preservation of neurocytoarchitecture in the ancient brain, which appeared shrunken and compact compared to a modern brain. Resolution of intermediate filaments (IFs) from protein aggregates took 2–12 months. Immunoassays on micro-dissected brain tissue homogenates revealed the preservation of the known protein topography for grey and white matter for type III (glial fibrillary acidic protein, GFAP) and IV (neurofilaments, Nfs) IFs. Mass spectrometry data could be matched to a number of peptide sequences, notably for GFAP and Nfs. Preserved immunogenicity of the prehistoric human brain proteins was demonstrated by antibody generation (GFAP, Nfs, myelin basic protein). Unlike brain proteins, DNA was of poor quality preventing reliable sequencing. These long-term data from a unique ancient human brain demonstrate that aggregate formation permits for the preservation of brain proteins for millennia.